Die Wirkung von Kompressionsstrümpfen auf die kapillare Filtrationsrate und Ödembildung - Wolff, O.; Wentel, T. D.; Reeder, S. W. I.; Neumann, H. A. M. (Phlebologie, 2011)
Increased ambulatory venous pressure is the key feature of chronic venous insufficiency, and causes capillary leakage and venous edema. This capillary leakage can be measured with plethysmography and is called the capillary filtration rate (CFR).Reduction of the CFR leads to less edema formation and improves the healing of venous ulcers.Aim: To show that the use of compression ulcer stockings reduces the CFR.Methods: The capillary filtration rate of both legs of 17 patients, 6 with chronic venous insufficiency and 11 healthy subjects was measured with both (day and night) stockings, only the night stocking and without stockings.Results: The reduction of the CFR was significant (p <0.0001) for the total population in the group wearing 2 stockings versus 1 stocking (CFR=0.019 vs. 0.084 ml/100 ml/min), 1 stocking versus no stocking (CFR=0.149 vs. 0.084 ml/100 ml/min) and 2 stockings versus no stockings (CFR=0.019 vs. 0.149 ml/100 ml/ min).Conclusion: Compression ulcer stockings are highly effective in reducing CFR and thus reducing edema formation, which leads to improved healing of venous ulcers.
Keywords: Capillary filtration; compression stockings; ulcer